Behavioural phenotypes in the classroom: a qualitative study of parental and teacher knowledge of classroom guidelines and teacher views on best practices. Issue 2 (13th January 2015) - Reilly, Colin; Murtagh, Lelia; Senior, Joyce
Abstract : Research suggests that genetic syndromes associated with intellectual disability often have specific cognitive and behavioural profiles. It has been suggested that educational approaches need to reflect these profiles. Parents (n = 381) and teachers (n = 204) of children with one of four syndromes, fragile X syndrome, Prader–Willi syndrome, Williams syndrome and velo‐cardio‐facial syndrome were surveyed. Syndromes were compared with respect to what parents and teachers had researched or been told with respect to appropriate educational approaches. Parent and teacher reports were subsequently compared with actual published guidelines on the syndromes. Teachers were also surveyed on what they felt were successful approaches based on actual experiences of teaching the children. Parent and teacher reports of efficacious strategies for supporting their children based on what they had been researched or been told differed across syndromes as might be anticipated. However, differences between parents and teachers and between parent/teacher reports and the published guidelines suggest that parent and teacher knowledge of guidelines is deficient and/or that parents and teachers are accessing knowledge elsewhere. With respect to teaching practices, there were much less differences between the syndromes than in the published guidelines indicating that differences between syndromes in guidelines may not be as evident in practice.